The role of grade in local recurrence and the disease-specific survival in chondrosarcomas. (May 2018) - Laitinen, M. K.; Stevenson, J. D.; Parry, M. C.; Sumathi, V.; Grimer, R. J.; Jeys, L. M.
Abstract : Aims: The purpose of this study was to describe the effect of histological grade on disease-specific survival in patients with chondrosarcoma. Patients and Methods: A total of 343 patients with a chondrosarcoma were included. The histological grade was assessed on the initial biopsy and on the resection specimen. Where the histology showed a mixed grade, the highest grade was taken as the definitive grade. When only small focal areas showed higher grade, the final grade was considered as both. Results: The concordance between the highest preoperative biopsy grading and the highest final grading of the resection specimen in total was only 43% (146/343). In 102 specimens (30%), a small number of cells or focal areas of higher grade were observed in contrast to the main histology. The disease-specific survival, stratified according to the predominant histological grade, showed greater variation than when stratified according to the highest grade seen in the resection specimen. Conclusion: The diagnostic biopsy in chondrosarcoma is unreliable in assessing the definitive grade and the malignant potential of the tumour. When categorizing the grade of the resection specimen, the prognosis for local recurrence and disease-specific survival should be based on the highest grade seen, even when seen in only a few cells. Cite this article: Bone Joint J 2018;100-B:662–6.